Produtores de Água na Microbacia do Manancial Córrego do Veado – Presidente Venceslau, São Paulo: potencialidades em questão - Kanevieskir, Thiciany [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The programs Water Producer and Water Mine are the starting point for the research, whose the main objective is to develop a study on the necessity and possibility to forming water producers in the Veado Creek Watershed Deer, located in Presidente Venceslau - Sao Paulo, in order to improve the quality and quantity of water from the spring. To this end, the implementation of programs in the spring, especially the Water Mine, developed by the State of Sao Paulo, could help change the situation in which degradation is the area of the watershed. The main methodological procedures were performed: survey and literature review, interviews with employees SEAAMA, CATI, interview with the president of the Association of Owners of Rural Watershed of Deer Creek; interview with landowners of the Fountain Creek Watershed Deer; work in the search field at the landfill to the DAE and the Association of Collectors of Recycled. We are dealing with issues such as the importance of the Code of forests with regard to the protection of water resources, decentralized management and participatory of water resources, Payment by Environmental Services, production of water, characterization and diagnosis of the environmental Microbacia of Wealth Córrego do Veado, sanitation of the municipality of Presidente Venceslau. Analyzed the current situation of the watershed of the spring, highlighting the main actions that have been performed by the municipality through the watershed program of the State of São Paulo City Hall and through the resources FEHIDRO. The obtained results allowed to demonstrate the need and the possibility of setting up the Project Mine Of Water in the watershed of the fountain and the interest of owners interviewed by adherence to the Project and the protection of the source

Os programas Produtor de Água e Mina D’Água são o ponto de partida para a realização da pesquisa, cujo objetivo principal é desenvolver um estudo sobre a necessidade e possibilidade de se formar produtores de água na Microbacia do Manancial Córrego do Veado, localizada em Presidente Venceslau, São Paulo, a fim de melhorar a qualidade e quantidade da água do manancial. Para tanto, a implantação dos programas na área do manancial, em especial o Mina D’Água, desenvolvido pelo Governo do Estado de São Paulo, pode vir a contribuir para alterar a situação de degradação em que se encontra a área do manancial. Os principais procedimentos metodológicos realizados foram: levantamento e análise bibliográfica; entrevistas com funcionários da SEAAMA, CATI; entrevista com o presidente da Associação dos Proprietários Rurais da Microbacia do Córrego do Veado; entrevista com proprietários rurais da Microbacia do Manancial Córrego do Veado; trabalhos de campo na área de pesquisa, ao aterro sanitário, ao DAE e à Associação de Catadores de Reciclados. Abordamos questões como a importância do Código Florestal com relação à proteção dos recursos hídricos, gestão descentralizada e participativa dos recursos hídricos, Pagamento por Serviços Ambientais, produção de água, caracterização e diagnóstico ambiental da Microbacia do Manancial Córrego do Veado, saneamento básico do município de Presidente Venceslau. Analisamos a situação atual da microbacia do manancial, destacando as principais ações que já foram realizadas pelo município por meio do Programa de Microbacias Hidrográficas do Estado de São Paulo e pela Prefeitura Municipal mediante recursos do FEHIDRO. Os resultados obtidos permitiram comprovar a necessidade e a possibilidade de implantação do Projeto Mina D’Água na microbacia do manancial e o interesse dos proprietários entrevistados pela adesão ao Projeto e a proteção do manancial
Keywords: Geografia; Abastecimento de água - Presidente Venceslau (SP); Microbacias Hidrográficas